'Doing it in the right order': childless men's intentions regarding family formation. (1st January 2022) - Hviid Malling, Gritt Marie; Pitsillos, Tryfonas; Tydén, Tanja; Hammarberg, Karin; Ziebe, Søren; Friberg, Britt; Schmidt, Lone
Abstract: In high-income countries, parental age at first birth has increased and this postponement increases the risk of involuntary childlessness or having fewer children than desired. This interview study was conducted in Denmark and Sweden among childless men ( n  = 29) in their last year of an education. The aim was to explore the role of individual and societal factors on fertility decision-making and men's reflections on barriers and enablers for earlier family formation. Data were analysed with thematic content analysis. Almost all participants wanted children in the future. Overall, there was a desire to follow the 'right chronology': get educated, having a stable relationship, employment and a good financial status before having children. While most men felt mature enough to have children, they were still not ready. Influences from within the inner social circle, societal expectations, the need for security and stability and being ready to give up freedom and individuality were factors that affected participants' preferred timing of parenthood. Most men did not have suggestions for how earlier family formation could be supported. Results suggest a gap between the ideal biological and ideal social age of family formation that may lead to unfulfilled parenthood aspirations.